Tuberculosis in combination with HIV infection and viral hepatitis: clinical case - O.D. Nikolayeva; T.V. Suprunenko (Civic Union "Communicable Diseases Intensive Care Association", 2024)
ABSTRACT. In recent years, there has been an increase in the number of cases of combined HIV/TB/VH (human immunodeficiency virus / tuberculosis / viral hepatitis) infection. Approaches to the treatment of these patients are changing with the advent of antiviral drugs for the treatment of hepatitis B and C. Treatment of VH in patients with TB increases the effectiveness of antituberculosis therapy by reducing the hepatotoxicity of antimycobacterial drugs. The interaction of antituberculosis, antiretroviral, and direct-acting antiviral drugs for the treatment of HCV was taken into account when managing a case of HIV/TB/HV. The article presents a case of effective treatment of a patient with combined HIV/TB/VH infection.